Is phenotypic canalization involved in the decline of the endemic Aquilegia thalictrifolia? Rethinking relationships between fluctuating asymmetry and species conservation status. Issue 4 (26th October 2015) - Abeli, Thomas; Zubani, Lino; Bonomi, Costantino; Parolo, Gilberto; Gargano, Domenico
Abstract: Fluctuating asymmetry (FA), the deviation from the normal symmetrical condition of a morphological trait having specific morphological symmetry, increases in response to environmental and genetic stress, is related to phenotypic plasticity and is considered a tool for monitoring a species conservation status. However, FA–stress relations are dependent on measured traits or species‐specific characteristics such as mating system and habitat. This study investigates the relationships between FA, genetic diversity, population size, density and individual fitness traits (plant height, fruit and seed set), in the endemic A quilegia thalictrifolia, a mixed breeder that is declining, but maintaining high levels of heterozygosity. Leaf and flower FA and other traits were investigated in 10 populations of A. thalictrifolia, the whole species range. As a result, we found similar patterns of FA in leaves and flowers between populations, indicating a homogenous level of stress between populations that differed for other traits. FA and the other traits were not related, including heterozygosity. Heterozygosity was not related to individual fitness traits with the exception of plant height. In accordance with other studies, we found that the role of FA as a tool for assessing the conservation status of a species or population should be reconsidered. However, we conclude that a low level of FA should not automatically be considered an indicator of good conservation status or low level of stress, because in species that evolved in highly stable environments it may indicate a scarce ability to plastically respond to environmental changes, as a consequence of environmental and genetic canalization. Further investigation of this point is needed. Abstract : A low level of fluctuating asymmetry may not automatically be considered an indicator of good conservation status or low level of stress. In species that evolved in highly stable environments it may indicate a scarce phenotypic plasticity as a consequence of environmental and genetic canalization.